DISYNCRO: Perceived roles of clinical study coordinators and data managers: results from a web-based survey of professionals from contract research organizations - Susanna Yedro; Elena Tinari; Daniele Napolitano; Giulia Wlderk; Eleonora Ribaudi; Luciana Giannone; Gianluca Ianiro; Mattia Bozzetti; Antonio Gasbarrini; Vincenzina Mora (Contemporary Clinical Trials Communications)
Introduction: The evolution of clinical trials has made it essential to introduce specific roles, such as Clinical Study Coordinator (CSC) and Data Manager (DM), into the research process. Their responsibilities sometimes overlap, creating operational challenges in the workplace. This study aims to determine how personnel at Contract Research Organizations (CROs) perceive the differences between the CSC and DM roles, assess their functional overlap, and identify areas where greater role clarity and training are needed to improve operational efficiency. Methods: An online survey instrument was used to gather data from CRO professionals through an internet-based questionnaire. The survey gathered sociodemographic data and included a knowledge assessment of 18 items and a 9-item role responsibilities section. Participants were stratified into three ability groups using Item Response Theory (IRT) analysis based on a Rasch model. McNemar's tests and non-parametric tests analyzed knowledge discrepancies and perceptual contradictions. Results: A total of 122 participants completed the survey. Most partecipants (98.4 %) identified the CSC as the primary figure within a research center, and 77.9 % considered the CSC essential for clinical trial execution. Regarding functional overlap, 57.4 % of respondents believed that the CSC could perform the duties of a DM, whereas only 42.6 % thought the DM could assume the CSC's responsibilities. Participants with lower levels of knowledge demonstrated a higher rate of contradictory responses, indicating greater difficulty distinguishing between the two roles. Conclusion: Study findings demonstrate an overwhelming preference for CSCs, who play a key versatile role in managing clinical trials. The insufficient theoretical understanding of the different duties of CSCs and DMs hampers operational efficiency. Establishing standard training programs combined with harmonization is essential to defining roles, enhancing teamwork, and providing quality clinical research practices.